Dual axis solar tracker and monitoring system based on internet of things - Yonis M. Yonis Buswig; Shanti Faridah Salleh; Al-Khalid Othman; Norhuzaimin Julai; Azuka Affam; Lennevey Kinidi; Hazrul Mohamed Basri; Kasumawati Lias (Institute of Advanced Engineering and Science, 2026)
In this paper, the application of internet of things (IoT) technology in development of a dual-axis solar tracking system is presented. Sting capacity of piezoelectric material is applied a footstep energy generation system. Using Arduino MEGA as the main controller for the system, light-dependent resistors (LDRs) have been used for sunlight detection and maximum light intensity. Two servo motors have been employed to rotate the solar panel towards the position of the sun as detected by the LDR. Ethernet Shield is used as an intermediary between the hardware device and the IoT monitoring system through the Cayenne platform. Alert notifications are included to inform a remote user through phone or mail (or both) when a sensor has reached a certain predefined event. There is a 21.97 increased energy output buy the proposed system as compared to the single-axis solar tracker. Further test results of the manufactured prototype indicate that solar tracker data can be transmitted simply and monitored directly online, and the solar tracker is capable of receiving commands from the IoT monitoring application.